Peran Dimensi Lokasi Wisata Terhadap Keputusan Berkunjung Wisatawan - Victor Ringhard Pattipeilohy; Jean Rosalina Asthenu (Univiversitas Dr. Djar Wattiheluw, 2023)
The success of the tourism industry is inseparable from the role of tourist sites that can attract the attention of tourists. The current research aims to examine the effect of the role of location dimensions namely access, traffic, visibility, and facilities on the decision to visit tourists to Paragliding attractions. The number of samples involved in the current research is 100 respondents using simple random sampling technique, and to test and analyze data using multiple linear regression analysis. The results showed that the role of the dimensions of access, traffic, visibility, and facilities had a positive and significant impact on the decision to visit tourists to tourist objects.